A TRANSLATION ANALYSIS OF BATIK TERMS IN BILINGUAL BOOK OF 50 TAHUN DANAR HADI SOLO - Auliya Fahma; Sumardiono Sumardiono (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2022)
The process of converting something written or spoken into another language is known astranslation. The objectives of this research are: (1) to identify the techniques implemented totranslate batik terms in bilingual book of 50 Tahun Danar Hadi Solo and (2) to analyze how thetranslation techniques implemented affect the translation quality in terms of accuracy,acceptability, and readability. The researcher here applied descriptive qualitative method and thetype is library research to find out and examine batik terms. The technique of collecting data iscontent analysis and interview. The result of this research presented that: 1) there were 53 batikterms translated by applying one translation technique, 2) there were 54 batik terms translated byapplying two or more translation techniques, 3) there were 107 data are accurate, 66 data areacceptable and 87 data are readable. Next, the researcher discovered 111 data as batik termswhich contain cultural and Javanese meaning in the target language. The outcome of thisresearch also presented that Established Equivalent was the most used translation technique bythe translator since all data contain equivalence between the source and target languages.Keywords: Translation, Cultural Term, Qualitative Research